Editor Note - siti annisa Nuhoni (Indonesian Journal of Physical Medicine & Rehabilitation, 2016)
Pain has become one of the major medical problem in the world including Indonesia. The problems emergedin various aspect, including physical, psychological, social, spiritual and cultural. While the prevalence canbe seen prominently in elderly population, pain does not spare the young one as well. It can be caused bydegenerative disease, activities, or even the process of growing in children.